THE INFLUENCE OF MANAGEMENT CONTROL SYSTEM ON COMPANY FINANCIAL PERFORMANCE: A MANAGEMENT ACCOUNTING PERSPECTIVE - Triasma, Citra; Mukhtaruddin, Mukhtaruddin (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
Management Control System (MCS) is a strategic tool that plays a role in improving a company's financial performance through optimizing operational efficiency, more effective resource allocation, and data-based decision making. This study aims to analyze the effect of MCS implementation on a company's financial performance from a management accounting perspective. Using a qualitative approach based on literature studies, this study explores the benefits and challenges in implementing MCS. The results show that MCS can improve a company's profitability, transparency, and accountability if implemented effectively and in line with business strategy. However, challenges such as employee resistance, lack of training, and high implementation costs are obstacles to optimizing MCS. This study also highlights the importance of the contingency theory and stakeholder theory approaches in adapting MCS to the dynamics of the business environment. Thus, the proper implementation of MCS can support the company's financial sustainability and provide a competitive advantage in an increasingly complex market.